2011
DOI: 10.9738/cc20.1
|View full text |Cite
|
Sign up to set email alerts
|

Three-Dimensional Vascular Anatomy Relevant to Oncologic Resection of Right Colon Cancer

Abstract: We analyzed data on the three-dimensional vascular anatomy of the right colon from the operative documents of 215 patients undergoing oncologic resection for right colon cancer. The right colic artery (RCA) was absent in 146 patients (67.9%), with the ileocolic artery (ICA) crossing the superior mesenteric vein (SMV) ventrally in 78 patients (36.3%). When the RCA was present, both the ICA and the RCA crossed the SMV ventrally in 44 patients (20.5%), dorsally in 10 patients (4.7%), the RCA crossed the SMV ventr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(19 citation statements)
references
References 16 publications
0
19
0
Order By: Relevance
“…The studies were published between 1909–2017, with a sample size ranging from 9 to 610 specimens. The superior mesenteric vessels and their branches were investigated by dissections of cadaveric specimens in 21 studies 15 , 16 , 22 27 , 29 , 38 , 39 , 44 , 45 , 49 , 52 , 54 59 , by imaging methods in 16 studies (CT − 13 studies 18 , 21 , 28 , 32 35 , 37 , 40 , 43 , 50 , 51 , 53 , MRI – one study 41 , CT and surgery – one study 20 , Angiography – one study 46 ), and by dissection during surgical procedures in eight studies (surgical dissection only – six studies 17 , 30 , 31 , 36 , 47 , 48 , surgical dissection and angiography – one study 42 , surgical and cadaveric dissection – one study 19 ).…”
Section: Resultsmentioning
confidence: 99%
“…The studies were published between 1909–2017, with a sample size ranging from 9 to 610 specimens. The superior mesenteric vessels and their branches were investigated by dissections of cadaveric specimens in 21 studies 15 , 16 , 22 27 , 29 , 38 , 39 , 44 , 45 , 49 , 52 , 54 59 , by imaging methods in 16 studies (CT − 13 studies 18 , 21 , 28 , 32 35 , 37 , 40 , 43 , 50 , 51 , 53 , MRI – one study 41 , CT and surgery – one study 20 , Angiography – one study 46 ), and by dissection during surgical procedures in eight studies (surgical dissection only – six studies 17 , 30 , 31 , 36 , 47 , 48 , surgical dissection and angiography – one study 42 , surgical and cadaveric dissection – one study 19 ).…”
Section: Resultsmentioning
confidence: 99%
“…Tajima et al [22] found a high rate (36%) of multiple middle colic arteries, more often double than triple. Our study confirms their latter finding but not the former.…”
Section: Discussionmentioning
confidence: 98%
“…The ileocolic artery often passes posteriorly to the superior mesocolic vein [22][23][24], which theoretically should result in a longer residual stump as a central tie is more difficult to achieve and surgeons often choose to divide the vessel after the crossing of the vein. In our series, the ileocolic artery passed posterior to the superior mesocolic vein in 69% of cases but surprisingly did not result in a longer stump length probably because the superior mesocolic vein was never exposed.…”
Section: Discussionmentioning
confidence: 99%